Groundwater Quality and It’s Distribution Features in the Right Bank of Nilwala Ganga- Sri Lanka (Badulla Oya and Kirama Oya Basins) - Piyadasa, Ranjana U. K.; Weerasinghe, K.D.N; Kumara, P.W.H (My University, 2006)
Groundwater monitoring in the Right Bank of Nilwala Ganga Basin - (Badulla oya and Kirama oya basins) was conducted during January to June 2006 to determine the hydro geological conditions by selecting 60 (sixty) dug wells where water level, electrical conductivity (EC), total dissolved solids (TDS) and pH was measured in two weeks interval.. Groundwater is the major water source in the study area, where shallow unconfined groundwater is used for domestic purposes and irrigation The study helped to prepare hydro geological map and the distribution of EC, TDS and pH maps using the GIS package MAPINFO. Hydro geological map help to identify recharge and discharge areas of the catchment. There exist a closed relationship is identified between topographical map & groundwater contour map. The pH of the groundwater remains between 4.5 – 6.5 and it usually decreases within a small range consequent to rains and EC fluctuation was in the range of 200 – 600 mS/cm.